Comparative evaluation of the efficacy of topical Amlexanox 5%, Triamcinolone Acetonide 0.1%, and Tacrolimus 0.03% in the treatment of oral erosive lichen planus - A double-blinded randomized clinical trial - Vaibhav Seth; Rajendra G Patil; Ganapathi Moger; Udita Singh; Abhinav Sharma; Smriti Saxena (Wolters Kluwer Medknow Publications, 2022)
Objective: The objective of this study was to evaluate the short-term efficacy and safety of the topical application of amlexanox paste with triamcinolone acetonide paste and tacrolimus paste in the treatment of oral erosive lichen planus. Study Design: This study was a randomized double-blinded placebo-controlled clinical trial. Forty patients aged 18-70 years with erosive oral lichen planus received amlexanox 5% paste (n = 10), triamcinolone acetonide 0.1% paste (n = 10), tacrolimus 0.03% paste (n = 10), and glycerin as placebo (n = 10) for 15 days. Outcome measures included pain using visual analog scale (VAS) scores, and the erosive area in cm2 was evaluated both before (baseline) and during the trial (i.e., days 7 and 15). Results: After 15 days of treatment, all the groups showed significant reductions in erosive areas and VAS scores (P <.001) except for the glycerin-treated group, where it was found to be non-significant. No systemic side effects and adverse reactions were observed in the present study. Conclusion: It was found that the topical application of 5% amlexanox paste appeared as effective as 0.1% triamcinolone acetonide paste and 0.03% tacrolimus paste in the treatment of oral erosive lichen planus.